Pacientes em processo diagnóstico de câncer de cabeça e pescoço: aspectos psicológicos, percepções e expectativas - Graner, Karen Mendes [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This study aimed to describe the sociodemographic characteristics, lifestyle, and physical and mental health status of patients with head and neck cancer, as well as identify their perceptions and expectations regarding care and diagnosis. 49 patients were evaluated before and after diagnosis communication as they were submitted to biopsies in two diagnostic oral centers. Before the diagnosis (moment 1), the sociodemographic and lifestyle variables were evaluated using a questionnaire and validated instruments to assess anxiety (State - Trait Anxiety Inventory, STAI), depression (Beck Depression Inventory, BDI) and alcohol abuse (Alcohol Use Disorders Identification Test, AUDIT); reason for examination, feelings, perception of the problem, and expectations were investigated through a structured interview. After cancer diagnosis (moment 2), 29 patients had some aspects reassessed: anxiety, depression levels, perceptions, feelings about the disease, and expectations towards medical and dental care. Were also investigated coping and satisfaction with the service received from dentists. Data collected during the interviews were categorized and a descriptive and bivariate analysis (Qui-square, fisher, Goodman and Wilcoson – p<0,05) to other variables. The initial sample consisted mostly of males (73.4%) (mean age of 59 years), with four and a half years of study, employed (40.8%), low income (53,0%), having a partner (61.2%), living with relatives (87.8%), having feelings of social support (83.7%) and a religion (93.9%), smoking (44.9%) and (45.0%) drinking habits, and classified their health as “good” (69.4%). The mean time between observation of symptoms and seeking for help was six months, which were mostly intraoral lesions (83.7%), referred by dentists (51.1%). Before diagnosis (Moment 1), women had a high prevalence for anxiety-trait (53.9%), state (61.5%) and depressive symptoms (46.2%). Men had a higher frequency of risky use of ...

O presente estudo identificou características sociodemográficas, da saúde física e mental, percepções e expectativas ao atendimento e diagnóstico de pacientes com suspeita de câncer de cabeça e pescoço. Avaliou-se 49 pacientes de dois centros de diagnóstico oral. O delineamento constou de dois Momentos: pré-biópsia (M1) e pósdiagnóstico (M2). No M1, investigaram-se dados sociodemográficos, apoio social e estilo de vida (questionário), sintomas ansiosos (Inventário de Ansiedade Traço- Estado, IDATE), depressivos (Inventário de Depressão de Beck, BDI) e uso de álcool (Alcohol Use Disorders Identification Test, AUDIT); motivo da consulta, sentimentos, percepção do problema e expectativas sobre diagnóstico e atendimento (entrevista). No M2, reavaliaram-se sintomas ansiosos (IDATE-Estado) e depressivos (BDI), percepções e sentimentos ao diagnóstico, enfrentamento, expectativas e a satisfação com o atendimento (entrevista) dos 29 pacientes com diagnóstico de câncer. As respostas às entrevistas foram categorizadas. Utilizou-se de análises descritivas e bivariadas (chi-quadrado ou exato de Fisher, Goodman e Wilcoxon – p<0.05). Resultados: na amostra total, predominaram: homens (73,4%), idade de 59 anos, 4,5 anos de estudo, ocupação remunerada (40,8%), rendimento de R$ 670,65, viver com companheiro 61,2% e com parentes 87,8%, relatar sentimento de apoio social 83,7%, ter religião 93,9%, tabagismo e etilismo 44,9%, ter problemas de saúde 45,0% e autoavaliação da “saúde boa” 69,4%. O tempo médio de observação da lesão foi de seis meses, sendo a maioria intraoral (83,7%) e encaminhados por dentistas 51,0%. No M1, 53,9% das mulheres foram consideradas caso para ansiedade-Traço, 61,5% para Estado e 46,2% para sintomas depressivos; e 36,1% dos homens apresentaram risco para de uso de álcool. Observou-se que 61,2% dos pacientes relataram percepções realistas sobre sua saúde, satisfação com atendimento ...
Keywords: Cabeça - Câncer; Pescoço - Câncer; Pacientes - Aspectos psicológicos; Ansiedade; Head Cancer; Neck Cancer